Using Landsat data for assessing forest cover change and fragmentation in Laljhadi corridor of Kanchanpur district, Nepal - Aryal, R. R.; Shrestha, H. L.; Khanal, S. (Banko Janakari, 2013)
The study, carried out at Laljhadi corridor in Kanchanpur district of Nepal, aimed at assessing forest cover change and fragmentation using multi-temporal Landsat data. Post classifi cation change detection was applied on temporal forest cover class datasets obtained by supervised classifi cation technique with maximum likelihood algorithm. The overall change analysis indicated a decreasing trend in forest cover. Statistics on selected landscape metrics were generated to quantify the change in spatial structure resulting from fragmentation. The analysis of the landscape metrics depicted increase in fragmentation over the analysis time period along with progression of deforestation. DOI: http://dx.doi.org/10.3126/banko.v21i2.9142 Banko Janakari Vol. 21, No. 2, 2011 Page: 40-44 Uploaded date: November 11, 2013